Unstable twin in body-centered cubic tungsten nanocrystals - Xiang Wang (Nature Portfolio, 2020)
Body-centred cubic metals rarely show twinning during deformation. Here, the authors use high resolution transmission electron microscopy to show tungsten, a body-centred cubic metal, spontaneously undergoes detwinning when unloaded.